The Quality of the Venezuelan Demoracy under Hugo Chavez (1999-2013) - Corrales, Javier; Hidalgo, Manuel (PARTECIPAZIONE E CONFLITTO, 2017)
Following the work of Morlino (2012) and Katz and Morlino (2012), we evaluate the quality of democracy in Venezuela under Hugo Chávez. We argue that by the end of this administration, Venezuela became a hybrid regime. In those instances in which operated as a democracy, institutional quality was low; in other instances, the regime exhibited clear autocratic features.